Counselling for peace - Salazar-Clemena, Rose Marie (Philippine Journal of Psychology, 1995)
On the basis of a survey of Filipino concepts of peace, the author proposes a framework consisting of these components: peace with God, with self, with others, with the nation, and with the world. Different spheres or levels of school attainment in each of these components are discussed, namely, Kapayapaang mapagsarili (egocentric peace), Kapayapang mapag-ayon (acquiescences peace), Kapayapaang mapagpalaya (liberating peace), Kapayapaang mapagtugon (responsive peace), and Kapayapaang mapagbuo (integrative peace). A holistic model for counseling for peace is then presented, with its goals and objectives, techniques, and approaches. Implications for counseling procedures are given.